A comparison between the Wingate anaerobic power test to both vertical jump and line drill tests in basketball players - Hoffman, J. R.; Epstein, S.; Einbinder, M.; Weinstein, Y. (The Journal of Strength and Conditioning Research, 2000)
The purpose of this study was to compare 2 sport-specific field tests common in the training programs of basketball players to a laboratory measure of anaerobic power. Nine 17-year-old members of the Israel National Youth Basketball Team participated in this investigation. Field tests included a countermovement jump (CMJ), a 15-second anaerobic jump test (APJT), and a sprint test to assess anaerobic power (line drill). The line drill was performed 3 times (T1, T2, and T3) with a 2-minute passive rest between each sprint. In addition, all subjects performed a 30-second Wingate anaerobic power test (WAnT) to determine peak power (PP), mean power (MP), and fatigue index (FIWAnT). Kendall tau () rank correlation analysis revealed moderate positive rank correlations between MP and both T1 and T2 ( = 0.61 and 0.54, respectively). No significant rank correlations were observed between PP and the line drill. Significant (p 0.05) positive rank correlations were noted between CMJ and both PP and MP ( = 0.59 and 0.76, respectively). However, only a poor relationship (p > 0.05) was observed between APJT and both PP and MP ( = 0.20 and 0.28, respectively). These results suggest that the line drill and jump tests may be acceptable field measures of anaerobic power specific for basketball players.